Characterization of the Hypercitrullination Reaction in Human Neutrophils and Other Leukocytes - Yebin Zhou; Tiziana Di Pucchio; Gary P. Sims; Nanette Mittereder; Tomas Mustelin (Mediators of Inflammation)
Autoantibodies against citrullinated proteins are diagnostic for rheumatoid arthritis. However, the molecular mechanisms driving protein citrullination in patients with rheumatoid arthritis remain poorly understood. Using two independent western blotting methods, we report that agents that trigger a sufficiently large influx of extracellular calcium ions induced a marked citrullination of multiple proteins in human neutrophils, monocytes, and, to a lesser extent, T lymphocytes and natural killer cells, but not B lymphocytes or dendritic cells. This response required 250–1,000 μM extracellular calcium and was prevented by EDTA. Other neutrophil activating stimuli, such as formyl-peptides, GM-CSF, IL-6, IL8, TNFα, or phorbol ester, did not induce any detectable increase in protein citrullination, suggesting that receptor-induced calcium mobilization is insufficient to trigger hypercitrullination. We conclude that loss of membrane integrity and subsequent influx of high levels of calcium, which can be triggered by perforin released from cytotoxic cells or complement mediated formation of membrane attack complexes in the joints of rheumatoid arthritis patients, are sufficient to induce extensive protein citrullination in immune cells, notably neutrophils. This mechanism may provide the citrullinated autoantigens that drive autoimmunity in this devastating disease.